Hypertensive heart disease: Benefit of carvedilol in hemodynamic, left ventricular remodeling, and survival. (January 2019) - Dominguez, Renata F; da Costa-Hong, Valeria A; Ferretti, Luan; Fernandes, Fabio; Bortolotto, Luiz A; Consolim-Colombo, Fernanda M; Egan, Brent M; Lopes, Heno F
Objectives: The aim of this study was to determine if carvedilol improved structural and functional changes in the left ventricle and reduced mortality in patients with hypertensive heart disease. Methods: Blood pressure, heart rate, echocardiographic parameters, and laboratory variables, were assessed pre and post treatment with carvedilol in 98 eligible patients. Results: Carvedilol at a median dose of 50 mg/day during the treatment period in hypertensive heart disease lowered blood pressure 10/10 mmHg, heart rate 10 beats/min, improved left ventricular ejection fraction from baseline to follow-up (median: 6 years) (36%–47%)) and reduced left ventricular end-diastolic and end-systolic dimensions (62 vs 56 mm; 53 vs 42 mm, respectively, all p-values <0.01). Left ventricular ejection fraction increased in 69% of patients. Patients who did not have improved left ventricular ejection fraction had nearly six-fold higher mortality than those that improved (relative risk; 5.7, 95% confidence interval: 1.3–25, p = 0.022). Conclusion: Carvedilol reduced cardiac dimensions and improved left ventricular ejection fraction and cardiac remodeling in patients with hypertensive heart disease. These treatment-related changes had a favorable effect on survival.